2018
DOI: 10.1039/c8cc00360b
|View full text |Cite
|
Sign up to set email alerts
|

Redox fusion of metal particles using deep eutectic solvents

Abstract: Alternating anodic and cathodic current pulses have been applied to a metal powder on an electrode surface to fuse the particles together. It is shown that homogeneous films can be electroformed with different morphologies depending on the size of the powder and the experimental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…DES is a fluid, usually composed of two or three inexpensive and safe components formed by hydrogen bonding of eutectic mixtures with melting points lower than that of each individual component . The physical and chemical properties of DES are very similar to those of ionic liquids, , which have a simple preparation, low cost, low toxicity, good solubility, and non-volatility. Recently, researchers have found that DES has excellent solubility for metal oxides even without a reducing agent or an extractant, which makes the research of DES in the field of spent LIB recycling more and more enthusiastic. Peeters et al prepared a DES that consisted of choline chloride (ChCl) and citric acid containing 35 wt % of water as an extraction agent, 98% Co and 93% Li could be extracted from lithium cobalt oxide (LiCoO 2 ) using Cu as the reducing agent . The use of reductants and post-treatment will make the metal extraction process more complex, while DES can optimize the process and be more environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…DES is a fluid, usually composed of two or three inexpensive and safe components formed by hydrogen bonding of eutectic mixtures with melting points lower than that of each individual component . The physical and chemical properties of DES are very similar to those of ionic liquids, , which have a simple preparation, low cost, low toxicity, good solubility, and non-volatility. Recently, researchers have found that DES has excellent solubility for metal oxides even without a reducing agent or an extractant, which makes the research of DES in the field of spent LIB recycling more and more enthusiastic. Peeters et al prepared a DES that consisted of choline chloride (ChCl) and citric acid containing 35 wt % of water as an extraction agent, 98% Co and 93% Li could be extracted from lithium cobalt oxide (LiCoO 2 ) using Cu as the reducing agent . The use of reductants and post-treatment will make the metal extraction process more complex, while DES can optimize the process and be more environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Zein Nanofibers were prepared separately in conventional and deep eutectic solvent using (Har-100*12, Matsusada Co., Tokyo, Japan) Electrospinning machine. Zein 25% (w/v) in 80% of Aq-EtOH was stirred for 2 h at 80 °C 21 . The DES was prepared by mixing Choline chloride and Furfuryl alcohol with molar ratio 2:1 and stirred well until a clear transparent solution was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…DESs are ion composite solutions formed from a hydrogen key receptor and hydrogen key supplier; they have many advantages, such as low price, easy access, easy synthesis, green and environmentally friendly degradability, non-toxicity, and low volatility [ 16 , 17 ]. DESs have been used in organic synthesis and (biological) catalysis [ 18 ], biochemistry [ 19 ], analytical chemistry [ 20 ], nanomaterials [ 21 ], and extraction processes [ 22 ]. However, there is no report on DESs for extracting polysaccharides from Bletilla striata .…”
Section: Introductionmentioning
confidence: 99%